Study on the Implementation of Service Concession Assets in Infrastructure Projects in Indonesia Based on PSAP 16 - Faishol, Adib; Putra, Yananto Mihadi (Baca Dulu Publisher, 2024)
This study examines the implementation of service concession assets in infrastructure projects in Indonesia, guided by the Public Sector Accounting Standard (PSAP) 16. The focus is on understanding the practical application of PSAP 16, which governs the accounting treatment of service concession arrangements, and analyzing the challenges faced by Indonesian public sector entities in applying these standards. Using a qualitative research approach, this study analyzes data from key stakeholders, including government agencies and project managers involved in infrastructure projects with service concession agreements. The findings highlight the compliance issues, operational challenges, and strategic adaptations necessary for aligning project implementation with PSAP 16 requirements. This research contributes to the literature by providing insights into the effectiveness of PSAP 16 in enhancing financial transparency and accountability in infrastructure project management. The study also offers practical recommendations for improving the adoption and implementation of PSAP 16, ensuring that service concession arrangements are accurately represented in public sector financial reporting.